Strategi Penguatan Nilai Demokrasi dan Nilai Nasionalis Bagi Siswa - Juwono, Hendro (MOMENTUM : Jurnal Sosial dan Keagamaan, 2024)
The development of nationalist values and democratic values of students is an important topic in education. Nationalist values and democracy can be developed through various approaches in schools and in society. The community and schools both have a big role in shaping the character and nature of nationalist and democratic values. Excessive use of gadgets at home can make students more isolated from their surroundings. They may interact more in the virtual world than in the real world, so the sense of community and attachment to local and national cultures can decrease. In addition, gadgets contain global content that can influence students' views and values. Content that is global and does not always reflect nationalist values can shift students' attention away from national culture and history. The purpose of writing the article is to describe the strategy of instilling democratic values and nationalist values for students. The method used is qualitative, with the type of literature research. The results of the research are strategies to strengthen democratic and nationalist values to students through the provision of citizenship education, ceremonial exercises with the introduction of material about independence, inviting students and students to historical sites, including the tombs of heroes. Siswa yang mendapat pembelajaran melalui Pendidikan Pancasila dan kewarganegaraan yang dikuatkan dengan melihat langsung situs-situs sejarah dapat menguatkan nilai demokrasi dan nasionalis tertanam di dalam sanubari siswa.